Management accounting practices in the Portuguese lodging industry - Santos, Luís Lima (2010)
Purpose - This paper aims to characterize management accounting techniques at the Portuguese lodging industry, identifying the techniques adopted and the determinants of adopting them and their adequacy for the decision-making process. It is also a purpose to understand the extent to which the industry adopts the Uniform System of Accounts for the Lodging Industry. Design/methodology/approach - The sample includes 35 hotels, which were analyzed in the years 2009 and 2010. Findings – Evidence is found supporting the fact management accounting is a tool incorporated in the daily management practices of hotels and useful to support the decision making process. The proportion used of traditional management accounting techniques is higher than the proportion of use of contemporary ones. The adoption of these techniques is influenced by the fact of the hotels being subsidiaries of a multinational hotel chain, as well as by their annual turnover. In Portugal, there is a weak use of USALI. It is more used in the large hotels and in hotels with a foreign control. Originality/Value – Management accounting supports hotels to improve their performance, thus becoming relevant to analyze management accounting practices used by them, particularly which instruments and techniques. In this context, this study, the first of its kind in Portugal, is justified with the increasing need for accurate and actual information of the accounting practices of the hotels operating in Portugal.